Evidence from Tm anomalies for non-CI refractory lithophile element proportions in terrestrial planets and achondrites. (1st March 2016) - Barrat, J.A.; Dauphas, N.; Gillet, P.; Bollinger, C.; Etoubleau, J.; Bischoff, A.; Yamaguchi, A.
Abstract: Thulium is a heavy rare earth element (REE) whose geochemical behavior is intermediate between Er and Yb, and that is not expected to be decoupled from these elements during accretion of planetary bodies and geological processes. However, irregularities in REE volatilities at higher temperature could have decoupled the REEs relative to one another during the early stages of condensation of the solar nebula. Indeed, positive Tm anomalies are found in some refractory inclusions from carbonaceous chondrites, and it is possible that large scale nebular reservoirs displaying positive or negative Tm anomalies were formed during the early history of the solar system. We analyzed a series of meteorites and terrestrial rocks in order to evaluate the existence of Tm anomalies in planetary materials. Relative to CIs (Ivuna-type carbonaceous chondrites), carbonaceous chondrites display unresolved or positive Tm anomalies, while most of the noncarbonaceous chondrites show slightly negative Tm anomalies. Quantification of these anomalies in terrestrial samples is complicated when samples display fractionated heavy REE patterns. Taking this effect into account, we show that the Earth, Mars, Vesta, the aubrite and ureilite parent bodies display small negative anomalies (Tm/Tm ∗ ≈ 0.975), very similar to those found in ordinary and enstatite chondrites. We suggest that a slight negative Tm anomaly relative to CI is a widespread feature of the materials from the inner solar system. This finding suggests that CI chondrites may not be appropriate for normalizing REE abundances of most planetary materials as they may be enriched in a high-temperature refractory component with non-solar composition. The presence of Tm anomalies at a bulk planetary scale is, to this day, the strongest piece of evidence that refractory lithophile elements are not present in constant CI proportions in planetary bodies.